PENGARUH INVESTASI AKTIVA TETAP TERHADAP LABA BERSIH PADA PERUSAHAAN PERKEBUNAN KELAPA SAWIT YANG TERDAFTAR DI BURSA EFEK INDONESIA - Malia, Abel; Iqbal, Johandri; Adinda, Pramesti Nurul (Journal of Applied Accounting And Business, 2025)
The influence of fixed asset investment on net profit of oil palm plantation companieslisted on the Indonesia Stock Exchange in 2019-2023. The data used in this study are secondary data, namely data obtained from the Indonesia Stock Exchange of companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. Data analysis uses quantitative data. Data analysis uses multiple linear regression methods. The results of the research show that fixed asset investment has a partial effect on net profits in oil palm plantation companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. And simultaneously fixed asset investment on net profit in oil palm plantation companies listed on the (IDX) in 2019-2023.